The influence of marketing on the sports betting attitudes and consumption behaviours of young men: implications for harm reduction and prevention strategies. Issue 1 (December 2017) - Deans, Emily; Thomas, Samantha; Derevensky, Jeffrey; Daube, Mike
Abstract Background Gambling can cause significant health and social harms for individuals, their families, and communities. While many studies have explored the individual factors that may lead to and minimise harmful gambling, there is still limited knowledge about the broader range of factors that may contribute to gambling harm. There are significant regulations to prevent the marketing of some forms of gambling but comparatively limited regulations relating to the marketing of newer forms of online gambling such as sports betting. There is a need for better information about how marketing strategies may be shaping betting attitudes and behaviours and the range of policy and regulatory responses that may help to prevent the risky or harmful consumption of these products. Methods We conducted qualitative, semi-structured interviews with 50 Australian men (aged 20–37 years) who gambled on sports. We explored their attitudes and opinions regarding sports betting marketing, the embedding of marketing within sports and other non-gambling community environments, and the implications this had for the normalisation of betting. Results Our findings indicate that most of the environments in which participants reported seeing or hearing betting advertisements were not in environments specifically designed for betting. Participants described that the saturation of marketing for betting products, including through sports-based commentary and sports programming, normalised betting. Participants described that the inducements offered by the industry were effective marketing strategies in getting themselves and other young men to bet on sports. Inducements were also linked with feelings of greater control over betting outcomes and stimulated some individuals to sign up with more than one betting provider. Conclusions This research suggests that marketing plays a strong role in the normalisation of gambling in sports. This has the potential to increase the risks and subsequent harms associated with these products. Legislators must begin to consider the cultural lag between an evolving gambling landscape, which supports sophisticated marketing strategies, and effective policies and practices which aim to reduce and prevent gambling harm.